Do different lipid emulsions affect brain development? A single-center retrospective analysis - Caruggi, Samuele; Calandrino, Andrea; Corradi, Benedetta; Battaglini, Marcella; Massirio, Paolo; Vinci, Francesco; Mongelli, Federica; Pepe, Alessia; Parodi, Alessandro; Malova, Mariya; Zoia, Agata; Severino, Mariasavina; et al. (Frontiers in Nutrition, 2026)
BackgroundPreterm birth is a critical period for brain development, as extrauterine factors can impair growth and myelination, thereby increasing the risk of neurodevelopmental impairment. Adequate nutrition and rapid weight gain are associated with better cognitive outcomes, and the choice of lipid emulsion during parenteral nutrition may influence these results. SMOFlipid®, enriched with omega-3 long-chain polyunsaturated fatty acids, could reduce inflammation and oxidative stress, potentially lowering bronchopulmonary dysplasia (BPD) risk. This study compared brain maturation at term-equivalent age (TEA) using MRI and neurodevelopment at 2 years in infants receiving either SMOFlipid® or Intralipid®.MethodsIn this single-center retrospective observational cohort study, we included all very low birth weight (VLBW) infants admitted to the NICU of our institution between 2017 and 2021. Infants who underwent brain MRI at term-equivalent age and completed neurodevelopmental assessment at 2 years were included, and those with severe brain lesions were excluded. Patients were categorized into two groups based on the lipid emulsion administered during parenteral nutrition. The primary outcome was neurodevelopment at 24 months of corrected age (CA). The secondary outcome was brain maturation assessed by the total maturation score (TMS) on magnetic resonance imaging (MRI).ResultsA total of 121 VLBW infants were included and categorized into two cohorts based on the lipid formulation administered: multi-component lipid emulsion (MLE) in 62 and soybean lipid emulsion (SLE) in 49 infants. TMS showed non-statistically significant differences among infants treated with SLE compared with those treated with MLE, as well as in neurodevelopmental outcomes assessed using Griffith’s scales.ConclusionDespite integrating brain imaging and clinical follow-up data, this study could not determine the optimal lipid emulsion for preterm infants.